Expressway LED transparent lens mask and preparation method thereof

By using multi-component collaborative design in the transparent mask material of highway LED display, combining PMMA-b-PGMA, Ce-ZnO quantum dots, random terpolymers, photochromic spiropyran modified silica nanoparticles and hyperbranched fluorinated polyethers, multiple challenges of the material in complex outdoor environments are solved, and efficient and economical comprehensive performance improvement is achieved.

CN119752086AActive Publication Date: 2025-04-04HUIZHOU ZONGHAN BOCHUANG TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510009719.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The transparent mask material of the highway LED display faces problems such as sunlight, ultraviolet rays, temperature changes, humidity fluctuations and pollutants accumulation in complex outdoor environments, resulting in reduced information clarity, shortened service life and increased maintenance costs.

Method used

Poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA) is used as the matrix, combining nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots, random ethylene-methyl acrylate-glycidyl methacrylate terpolymer, photochromic spiropyran derivative modified silica nanoparticles and hyperbranched fluorinated polyethers, the material's high light transmittance, UV resistance, self-healing ability, intelligent anti-glare function and self-cleaning effect through multi-component collaborative design.

Benefits of technology

The comprehensive performance improvement of the material is achieved, including high light transmittance, long-term stability, fast self-repair, wide intelligent dimming range and excellent self-cleaning effect, which significantly improves the service life and information transmission efficiency of highway LED displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005228009670000073
    Figure BDA0005228009670000073
  • Figure BDA0005228009670000081
    Figure BDA0005228009670000081
  • Figure BDA0005228009670000222
    Figure BDA0005228009670000222
Patent Text Reader

Abstract

The invention relates to the technical field of lens masks, in particular to an expressway LED transparent lens mask and a preparation method thereof.The expressway LED transparent lens mask is prepared from, by weight, 80-90 parts of poly (methyl methacrylate)-b-poly (glycidyl methacrylate) block copolymer (PMMA-b-PGMA); 0.5 to 2.0 parts of nano-scale cerium doped zinc oxide (Ce-ZnO) quantum dots; 5 to 10 parts of a random ethylene-methyl acrylate-glycidyl methacrylate terpolymer; 1 to 3 parts of photochromic spiropyrane derivative modified silicon dioxide nanoparticles; according to the present invention, the high light transmittance is ensured, the active sites are provided through the PGMA block so as to easily achieve the uniform dispersion and the chemical bonding of other functional components, and the nano-scale cerium-doped zinc oxide (Ce-ZnO) quantum dots are introduced so as to achieve the efficient ultraviolet ray blocking and the light stability;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lens masks, and in particular to a highway LED transparent lens mask and a preparation method thereof. Background Art

[0002] With the rapid development of intelligent transportation systems, highway LED displays have become important equipment for providing real-time traffic information and safety warnings. However, these displays are exposed to complex outdoor environments for a long time and face many challenges. First, strong sunlight and ultraviolet radiation can cause aging and yellowing of the display mask material, affecting the clarity and readability of the information. Second, frequent temperature changes and humidity fluctuations can easily cause microcracks in the mask material, reducing its service life. Furthermore, the accumulation of pollutants such as rain, snow, and dust can seriously affect the display effect and increase maintenance costs. In addition, the glare problem under strong light at night has always plagued the driver's visual comfort and driving safety.

[0003] In the prior art, commonly used transparent mask materials such as polymethyl methacrylate (PMMA) or polycarbonate (PC) have good light transmittance, but perform poorly in terms of UV resistance, self-cleaning and anti-glare. Some improvement schemes, such as adding UV absorbers or applying anti-reflective coatings, have improved in some aspects, but often sacrifice other properties of the material. For example, adding UV absorbers may reduce the light transmittance of the material, while applying anti-reflective coatings may affect the weather resistance of the material. In addition, these methods can usually only solve a single problem and cannot comprehensively improve the comprehensive performance of the material.

[0004] Therefore, there is an urgent need to develop new highway LED transparent lens mask materials that can simultaneously possess excellent light transmittance, UV resistance, self-repairing ability, intelligent anti-glare function and self-cleaning effect to meet the long-term use requirements in complex outdoor environments. Summary of the invention

[0005] The present invention aims at the above problems and proposes an innovative highway LED transparent lens mask and a preparation method thereof.

[0006] The object of the present invention is to provide a highway LED transparent lens mask, which comprises the following components in parts by weight:

[0007] 80-90 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0008] 0.5-2.0 parts of nano-sized cerium-doped zinc oxide Ce-ZnO quantum dots;

[0009] 5-10 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0010] 1-3 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0011] 1-3 parts of hyperbranched fluorinated polyether.

[0012] Specifically, the molecular weight of the poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA) is 70,000-80,000 g / mol, and the block ratio of PMMA:PGMA is 7.5:2.5 to 8.5:1.5.

[0013] Specifically, the particle size of the nano-scale cerium-doped zinc oxide Ce-ZnO quantum dots is 5-10 nm, and the cerium doping amount is 1-5 mol%.

[0014] Specifically, the content of glycidyl methacrylate in the random ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 7.5-8.5 wt %, and the melt index (190° C. / 2.16 kg) is 6-8 g / 10 min.

[0015] Specifically, the particle size of the photochromic spiropyran derivative-modified silica nanoparticles is 20-50 nm, and the spiropyran modification density is 0.5-1.0 μmol / m 2 .

[0016] Specifically, the molecular weight of the hyperbranched fluorinated polyether is 2000-3000 g / mol, and the hydroxyl value is 155-175 mgKOH / g.

[0017] The method for preparing the highway LED transparent lens mask of the formula comprises the following steps:

[0018] (1) Preparation of nanoscale cerium-doped zinc oxide Ce-ZnO quantum dots:

[0019] a) In a 250 mL three-necked round-bottom flask, add 150 mL of anhydrous ethanol;

[0020] b) adding 10.0-12.0 mmol of zinc acetate dihydrate and 0.2-0.4 mmol of cerium (III) acetate hydrate, stirring and dissolving;

[0021] c) In another beaker, dissolve 20-24 mmol of sodium hydroxide in 50 mL of anhydrous ethanol;

[0022] d) In an ice bath at 0-5°C and under nitrogen protection, slowly add the sodium hydroxide solution to the acetate solution at a rate of 2-3 mL / min using a constant pressure dropping funnel while maintaining stirring at 900-1100 rpm;

[0023] e) After the dropwise addition was completed, the reaction temperature was raised to 25±2°C and the reaction was continued with stirring for 3 hours;

[0024] f) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous ethanol and deionized water three times each;

[0025] g) drying the obtained product in a vacuum oven at 80±2°C for 10 hours with the vacuum degree maintained at 0.1-0.05MPa;

[0026] (2) Preparation of Silica Nanoparticles Modified with Photochromic Spiropyran Derivatives:

[0027] a) In a 500 mL three-necked round-bottom flask, add 250 mL of anhydrous ethanol, 15 mL of ammonia water (28-30%) and 7 mL of deionized water;

[0028] b) under nitrogen protection, stirring at 600-700 rpm, slowly adding 20 mL of tetraethyl orthosilicate (TEOS) at a rate of 1-2 mL / min using a constant pressure dropping funnel, and reacting at room temperature (25±2°C) for 5 hours;

[0029] c) separating the silica nanoparticles by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous ethanol three times;

[0030] d) dispersing the nanoparticles in 250 mL of anhydrous toluene, adding 3 g of (3-glycidylpropoxy)trimethoxysilane, and reacting under reflux at 80±2° C. for 10 hours under nitrogen protection;

[0031] e) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous toluene and anhydrous ethanol three times each;

[0032] f) dispersing the modified nanoparticles in 250 mL of anhydrous N,N-dimethylformamide (DMF);

[0033] g) adding 2 g of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid;

[0034] h) react at 85±2°C for 18 hours under nitrogen protection;

[0035] i) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with DMF and anhydrous ethanol three times each;

[0036] j) drying the obtained product in a vacuum oven at 60±2°C for 18 hours with the vacuum degree maintained at 0.1-0.05MPa;

[0037] (3) Preparation of composite materials:

[0038] a) In a 1L three-necked round-bottom flask, add 500mL of tetrahydrofuran (THF);

[0039] b) adding 85 parts by weight of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA), stirring and dissolving at 25±2° C. for 5 hours at a stirring speed of 300-400 rpm;

[0040] c) under the condition of ultrasonic dispersion (power 40-50W, frequency 40kHz), 1.5 parts by weight of Ce-ZnO quantum dot suspension (preliminarily dispersed in 50mL THF) was slowly added, and ultrasonic dispersion was performed for 45 minutes;

[0041] d) adding 2 parts by weight of a suspension of silica nanoparticles modified with a photochromic spiropyran derivative (previously dispersed in 50 mL of THF), and continuing ultrasonic dispersion for 45 minutes;

[0042] e) adding 7.5 parts by weight of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer, stirring and dissolving at 25±2° C. for 3 hours at a stirring speed of 300-400 rpm;

[0043] f) Finally, add 2 parts by weight of hyperbranched fluorinated polyether, and stir evenly at 25±2° C. for 3 hours at a stirring speed of 300-400 rpm;

[0044] g) pouring the obtained uniform solution into a 40 cm×40 cm×1 cm polytetrafluoroethylene mold;

[0045] h) Slowly evaporate the solvent in a fume hood at 25±2°C for 36 hours;

[0046] i) The initially formed film is placed in a vacuum oven at 70±2° C. and dried for 18 hours with the vacuum degree maintained at 0.1-0.05 MPa to remove the residual solvent.

[0047] Specifically, the method also includes the following hot pressing steps:

[0048] a) cutting the dried composite film into squares of 30 cm×30 cm;

[0049] b) placing the film between two 40 cm × 40 cm, 1 cm thick polished stainless steel plates (surface roughness Ra ≤ 0.2 μm);

[0050] c) placing the entire assembly into a heat press;

[0051] d) Raise the temperature to 180±2°C at a rate of 8°C / min;

[0052] e) At 180±2℃, apply a pressure of 20±1MPa for 45 minutes;

[0053] f) Maintaining the pressure, slowly cool to 25±2°C at a rate of 2°C / min.

[0054] Specifically, the following surface treatment steps are also included:

[0055] a) Place the hot-pressed mask in a closed box filled with nitrogen (nitrogen purity ≥ 99.99%);

[0056] b) Use UV lamp with a wavelength of 365±5nm and a light intensity of 7.5±0.5mW / cm 2 ;

[0057] c) Irradiate at 30±2°C for 30 minutes to activate the photochromic groups on the surface.

[0058] Specifically, the following post-processing steps are also included:

[0059] a) preparing a 3 wt % hydrofluoric acid solution (using 40 % hydrofluoric acid);

[0060] b) Immerse the mask in hydrofluoric acid solution for 30±2 seconds;

[0061] c) Immediately rinse with deionized water (conductivity ≤ 1 μS / cm) for 4 minutes;

[0062] d) Wipe the surface with a Class 100 cleanroom dust-free cloth;

[0063] e) Dry in a vacuum oven at 70±2°C for 3 hours with the vacuum degree maintained at 0.1-0.05MPa.

[0064] The present invention has the following beneficial effects:

[0065] First, the use of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA) as the matrix not only ensures high transmittance, but also provides active sites through the PGMA block, which is conducive to the uniform dispersion and chemical bonding of other functional components. Secondly, the introduction of nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots, using its unique band structure and the synergistic effect of cerium elements, achieves efficient UV blocking and light stability. Furthermore, the addition of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer forms a dynamic covalent bond network, giving the material excellent self-healing ability. In addition, the introduction of silica nanoparticles modified by photochromic spiropyran derivatives realizes intelligent anti-glare function through light-induced molecular configuration changes. Finally, the addition of hyperbranched fluorinated polyether (Hyperbranched fluorinated polyether) creates a superhydrophobic effect similar to the lotus leaf surface by forming a nanoscale phase separation structure on the surface of the material, greatly improving the self-cleaning ability of the material.

[0066] This multi-component collaborative design not only solves the performance trade-off problem that may be caused by the improvement of a single function, but also produces a series of unexpected synergistic effects through the interaction between the components. For example, the interaction between the PGMA block of PMMA-b-PGMA and Ce-ZnO quantum dots not only enhances the material's UV resistance, but also improves the material's mechanical strength. The interaction between the photochromic spiropyran-modified silica nanoparticles and the PGMA block significantly improves the response speed and dimming range of the smart anti-glare.

[0067] From a molecular perspective, this synergistic effect is due to the carefully designed molecular structure and functional group distribution. The epoxy groups in PMMA-b-PGMA provide chemical bonding sites for other components, while the hydroxyl groups on the surface of Ce-ZnO quantum dots can undergo a ring-opening reaction with the epoxy groups to form stable chemical bonds. The glycidyl methacrylate units in the random terpolymer can not only form covalent bonds with the matrix, but also participate in the construction of a dynamic cross-linked network. The photochromic spiropyran molecules form stable bonds with the surface of silica nanoparticles through silane coupling agents, ensuring their uniform distribution and long-lasting performance in the matrix. The hyperbranched structure and terminal hydroxyl groups of the hyperbranched fluorinated polyether enable it to form physical entanglements and chemical bonds with the matrix, while forming a nanostructure with low surface energy on the surface.

[0068] This multi-level, multi-scale synergistic mechanism not only ensures the effective performance of the material's various functions, but also produces performance improvements beyond expectations. For example, after 2,000 hours of xenon lamp accelerated aging, the material's transmittance only dropped by 1.6%, far better than traditional materials; the self-repair speed was significantly accelerated, and a 100μm wide scratch could be repaired within 2 hours; the intelligent dimming range was expanded to 30%, 20-50% higher than expected; the water contact angle was as high as 158°, showing an excellent self-cleaning effect.

[0069] In summary, the present invention has successfully developed a multifunctional collaborative and high-performance highway LED transparent lens mask material by deeply understanding the cutting-edge knowledge of materials science, optics, polymer chemistry and nanotechnology. This innovation not only solves the multiple challenges faced by the existing technology, but also provides new ideas and methods for the development of a new generation of intelligent and durable transparent protective materials. The success of this invention will greatly improve the service life and information transmission efficiency of highway LED display screens, and make important contributions to improving road safety and traffic efficiency. In addition, this concept and method of multifunctional collaborative design is also expected to find wide application in the fields of architectural glass, automobile windshields, etc., and promote technological progress in related industries. DETAILED DESCRIPTION

[0070] In the highway LED transparent lens mask of the present invention, poly (methyl methacrylate) -b-poly (glycidyl methacrylate) block copolymer (PMMA-b-PGMA), trade name: Plexiglas VS-UVT brand: Plexiglas VS-UVT 100, molecular weight Mn = 75,000 ± 5,000 g / mol, block ratio PMMA: PGMA = 7.5: 2.5 to 8.5: 1.5, light transmittance ≥ 92% (3mm thickness, 550nm wavelength), refractive index additional 1.49 ± 0.01 (20 ° C, 589nm) glass transition temperature: 105 ± 2 ° C; random ethylene-methyl acrylate-glycidyl methacrylate terpolymer is a self-repairing and toughening agent, trade name AX8900, GMA content is 8±0.5wt%, melt index (190℃ / 2.16kg) is 6-8g / 10min; density is 0.94±0.01g / cm 3 ; Vicat softening point is 60±2℃; elongation at break>700%; hyperbranched fluorinated polyether, trade name Z-Tetraol, molecular weight Mn = 2200 ± 200 g / mol, hydroxyl value 160 ± 5 mgKOH / g viscosity (20 ° C) 80-120 cSt; surface tension (20 ° C) 25 ± 2 mN / m, thermal decomposition temperature > 290 ° C. The structural formula is as follows:

[0071]

[0072] Example 1

[0073] This embodiment provides a highway LED transparent lens mask and a preparation method thereof. The formula includes the following components by weight:

[0074] 80 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0075] 0.5 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0076] 5 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0077] 1 part of silica nanoparticles modified with photochromic spiropyran derivatives;

[0078] 1 part of hyperbranched fluorinated polyether.

[0079] The molecular weight of PMMA-b-PGMA is 70,000 g / mol, and the block ratio of PMMA:PGMA is 7.5:2.5. The particle size of Ce-ZnO quantum dots is 5 nm, and the cerium doping amount is 1 mol%. The content of glycidyl methacrylate in the random terpolymer is 7.5 wt%, and the melt index (190 ° C / 2.16 kg) is 6 g / 10 min. The particle size of the photochromic spiropyran-modified silica nanoparticles is 20 nm, and the spiropyran-modified density is 0.5 μmol / m 2 The molecular weight of the hyperbranched fluorinated polyether is 2000 g / mol and the hydroxyl value is 155 mg KOH / g.

[0080] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0081] First, nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots were prepared. In a 250 mL three-necked round-bottom flask, 150 mL of anhydrous ethanol was added, followed by 10.0 mmol of zinc acetate dihydrate and 0.2 mmol of cerium (III) acetate hydrate, and stirred to dissolve. In another beaker, 20 mmol of sodium hydroxide was dissolved in 50 mL of anhydrous ethanol. In a 0 ° C ice bath and nitrogen protection, the sodium hydroxide solution was slowly added to the acetate solution at a rate of 2 mL / min using a constant pressure dropping funnel, while maintaining stirring at 900 rpm. After the addition was completed, the reaction temperature was raised to 25 ° C, and the reaction was continued to stir for 3 hours. Subsequently, the product was separated by centrifugation at 7000 rpm for 15 minutes, and washed 3 times with anhydrous ethanol and deionized water respectively. Finally, the obtained product was placed in an 80 ° C vacuum oven and dried for 10 hours, and the vacuum degree was maintained at 0.1 MPa.

[0082] Secondly, prepare photochromic spiropyran derivative modified silica nanoparticles. In a 500mL three-necked round-bottom flask, add 250mL of anhydrous ethanol, 15mL of ammonia (28-30%) and 7mL of deionized water. Under nitrogen protection, stir at 600rpm, slowly add 20mL of tetraethyl orthosilicate (TEOS) at a rate of 1mL / min using a constant pressure dropping funnel, and react at room temperature (25°C) for 5 hours. Then, centrifuge at 7000rpm for 15 minutes to separate the silica nanoparticles and wash them 3 times with anhydrous ethanol. Disperse the nanoparticles in 250mL of anhydrous toluene, add 3g (3-glycidyl propoxy) trimethoxysilane, and reflux at 80°C for 10 hours under nitrogen protection. Centrifuge at 7000rpm for 15 minutes to separate the product again, and wash it 3 times with anhydrous toluene and anhydrous ethanol respectively. The modified nanoparticles were dispersed in 250 mL of anhydrous N,N-dimethylformamide (DMF), and 2 g of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid were added. Under nitrogen protection, the reaction was carried out at 85°C for 18 hours. Finally, the product was separated by centrifugation at 7000 rpm for 15 minutes, washed 3 times with DMF and anhydrous ethanol each, and the resulting product was placed in a vacuum oven at 60°C and dried for 18 hours, with the vacuum degree maintained at 0.1 MPa. The chemical structure of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] is as follows

[0083]

[0084] Next, prepare the composite material. In a 1L three-necked round-bottom flask, add 500mL tetrahydrofuran (THF), then add 80 parts by weight of PMMA-b-PGMA, stir and dissolve at 25°C for 5 hours, and the stirring speed is 300rpm. Under the condition of ultrasonic dispersion (power 40W, frequency 40kHz), slowly add 0.5 parts by weight of Ce-ZnO quantum dot suspension (pre-dispersed in 50mL THF), and ultrasonically disperse for 45 minutes. Subsequently, add 1 part by weight of silica nanoparticle suspension modified by photochromic spiropyran derivative (pre-dispersed in 50mL THF), and continue ultrasonic dispersion for 45 minutes. Add 5 parts by weight of random ethylene-methyl acrylate-methacrylate glycidyl ester terpolymer, stir and dissolve at 25°C for 3 hours, and the stirring speed is 300rpm. Finally, add 1 part by weight of hyperbranched fluorinated polyether, stir evenly at 25°C for 3 hours, and the stirring speed is 300rpm. The obtained uniform solution was poured into a 40 cm × 40 cm × 1 cm polytetrafluoroethylene mold, and the solvent was slowly evaporated at 25° C. for 36 hours in a fume hood. The initially formed film was placed in a vacuum oven at 70° C. and dried for 18 hours with the vacuum degree maintained at 0.1 MPa to remove the residual solvent.

[0085] The hot pressing molding steps are as follows: Cut the dried composite film into a 30cm×30cm square and place it between two 40cm×40cm, 1cm thick polished stainless steel plates (surface roughness Ra≤0.2μm). Put the entire assembly into a hot press and heat it to 180℃ at a rate of 8℃ / min. Apply a pressure of 20MPa at 180℃ for 45 minutes. Maintain the pressure and slowly cool it to 25℃ at a rate of 2℃ / min.

[0086] The surface treatment steps are as follows: Place the hot-pressed mask in a sealed box filled with nitrogen (nitrogen purity ≥ 99.99%). Use a UV lamp with a wavelength of 365nm and a light intensity of 7.5mW / cm 2 , and irradiated at 30 °C for 30 min to activate the photochromic groups on the surface.

[0087] Finally, a post-treatment step was performed: a 3wt% hydrofluoric acid solution was prepared (using 40% hydrofluoric acid). The mask was immersed in the hydrofluoric acid solution for 30 seconds and immediately rinsed with deionized water (conductivity ≤ 1μS / cm) for 4 minutes. The surface was wiped with a dust-free cloth from a Class 100 clean room and dried in a vacuum oven at 70°C for 3 hours, with the vacuum degree maintained at 0.1MPa.

[0088] Preferably, in an embodiment of the present invention, PMMA-b-PGMA is used as a matrix material, which not only provides excellent light transmittance, but also forms chemical bonds with other components through the epoxy groups of the PGMA block, thereby enhancing the overall performance of the material. Ce-ZnO quantum dots are used as anti-ultraviolet additives, and their nanoscale ensures uniform dispersion while maintaining the high light transmittance of the material. The random terpolymer provides self-healing ability and toughening effect through a dynamic covalent bond network, significantly improving the durability of the material. Photochromic spiropyran-modified silica nanoparticles realize intelligent anti-glare function, automatically adjust light transmittance under strong light, and improve driving safety. The introduction of hyperbranched fluorinated polyethers gives the material an excellent self-cleaning effect and reduces maintenance costs.

[0089] Example 2

[0090] This embodiment provides another highway LED transparent lens mask and a preparation method thereof. The formula includes the following components by weight:

[0091] 85 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0092] 1.25 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0093] 7.5 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0094] 2 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0095] 2 parts of hyperbranched fluorinated polyether.

[0096] The molecular weight of PMMA-b-PGMA is 75,000 g / mol, and the block ratio of PMMA:PGMA is 8:2. The particle size of Ce-ZnO quantum dots is 7.5 nm, and the cerium doping amount is 3 mol%. The content of glycidyl methacrylate in the random terpolymer is 8 wt%, and the melt index (190 ° C / 2.16 kg) is 7 g / 10 min. The particle size of the photochromic spiropyran-modified silica nanoparticles is 35 nm, and the spiropyran-modified density is 0.75 μmol / m 2 The molecular weight of the hyperbranched fluorinated polyether is 2500 g / mol and the hydroxyl value is 165 mg KOH / g.

[0097] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0098] First, nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots were prepared. In a 250 mL three-necked round-bottom flask, 150 mL of anhydrous ethanol was added, followed by 11.0 mmol of zinc acetate dihydrate and 0.3 mmol of cerium (III) acetate hydrate, and stirred to dissolve. In another beaker, 22 mmol of sodium hydroxide was dissolved in 50 mL of anhydrous ethanol. In a 2.5 ° C ice bath and nitrogen protection, the sodium hydroxide solution was slowly added to the acetate solution at a rate of 2.5 mL / min using a constant pressure dropping funnel, while maintaining stirring at 1000 rpm. After the addition was completed, the reaction temperature was raised to 25 ° C, and the reaction was continued to stir for 3 hours. Subsequently, the product was separated by centrifugation at 7500 rpm for 15 minutes, and washed 3 times with anhydrous ethanol and deionized water respectively. Finally, the obtained product was placed in an 80 ° C vacuum oven and dried for 10 hours, and the vacuum degree was maintained at 0.075 MPa.

[0099] Secondly, prepare photochromic spiropyran derivative modified silica nanoparticles. In a 500mL three-necked round-bottom flask, add 250mL of anhydrous ethanol, 15mL of ammonia (28-30%) and 7mL of deionized water. Under nitrogen protection, stir at 650rpm, slowly add 20mL of tetraethyl orthosilicate (TEOS) at a rate of 1.5mL / min using a constant pressure dropping funnel, and react at room temperature (25°C) for 5 hours. Then, centrifuge at 7500rpm for 15 minutes to separate the silica nanoparticles and wash them 3 times with anhydrous ethanol. Disperse the nanoparticles in 250mL of anhydrous toluene, add 3g (3-glycidyl propoxy) trimethoxysilane, and reflux at 80°C for 10 hours under nitrogen protection. Centrifuge at 7500rpm for 15 minutes to separate the product again, and wash it 3 times with anhydrous toluene and anhydrous ethanol respectively. The modified nanoparticles were dispersed in 250 mL of anhydrous N, N-dimethylformamide (DMF), and 2 g of 1', 3'-dihydro-1', 3', 3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid were added. The reaction was carried out at 85 ° C for 18 hours under nitrogen protection. Finally, the product was separated by centrifugation at 7500 rpm for 15 minutes, washed with DMF and anhydrous ethanol three times each, and the obtained product was placed in a vacuum oven at 60 ° C for 18 hours, and the vacuum degree was maintained at 0.075 MPa.

[0100] Next, prepare the composite material. In a 1L three-necked round-bottom flask, add 500mL tetrahydrofuran (THF), then add 85 parts by weight of PMMA-b-PGMA, stir and dissolve at 25°C for 5 hours, and the stirring speed is 350rpm. Under ultrasonic dispersion (power 45W, frequency 40kHz), slowly add 1.25 parts by weight of Ce-ZnO quantum dot suspension (pre-dispersed in 50mLTHF), and ultrasonically disperse for 45 minutes. Subsequently, add 2 parts by weight of silica nanoparticle suspension modified by photochromic spiropyran derivative (pre-dispersed in 50mLTHF), and continue ultrasonic dispersion for 45 minutes. Add 7.5 parts by weight of random ethylene-methyl acrylate-methacrylate glycidyl ester terpolymer, stir and dissolve at 25°C for 3 hours, and the stirring speed is 350rpm. Finally, add 2 parts by weight of hyperbranched fluorinated polyether, stir evenly at 25°C for 3 hours, and the stirring speed is 350rpm. The obtained uniform solution was poured into a 40 cm × 40 cm × 1 cm polytetrafluoroethylene mold, and the solvent was slowly evaporated at 25° C. for 36 hours in a fume hood. The initially formed film was placed in a vacuum oven at 75° C. and dried for 18 hours with the vacuum degree maintained at 0.075 MPa to remove the residual solvent.

[0101] The hot pressing molding steps are as follows: Cut the dried composite film into a 30cm×30cm square and place it between two 40cm×40cm, 1cm thick polished stainless steel plates (surface roughness Ra≤0.2μm). Put the entire assembly into a hot press and heat it to 185℃ at a rate of 9℃ / min. At 185℃, apply a pressure of 22.5MPa for 52.5 minutes. Maintain the pressure and slowly cool it to 25℃ at a rate of 2.5℃ / min.

[0102] The surface treatment steps are as follows: Place the hot-pressed mask in a sealed box filled with nitrogen (nitrogen purity ≥ 99.99%). Use a UV lamp with a wavelength of 365nm and a light intensity of 8.75mW / cm 2 , and irradiated at 35 °C for 35 min to activate the photochromic groups on the surface.

[0103] Finally, a post-treatment step was performed: a 3.5wt% hydrofluoric acid solution was prepared (using 40% hydrofluoric acid). The mask was immersed in the hydrofluoric acid solution for 35 seconds and immediately rinsed with deionized water (conductivity ≤ 1μS / cm) for 4.5 minutes. The surface was wiped with a dust-free cloth from a Class 100 clean room and dried in a vacuum oven at 75°C for 3.5 hours, with the vacuum degree maintained at 0.075MPa.

[0104] Example 3

[0105] This embodiment provides a third highway LED transparent lens mask and a preparation method thereof. The formula includes the following components by weight:

[0106] 90 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0107] 2.0 parts of nano-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0108] 10 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0109] 3 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0110] 3 parts of hyperbranched fluorinated polyether.

[0111] The molecular weight of PMMA-b-PGMA is 80,000 g / mol, and the block ratio of PMMA:PGMA is 8.5:1.5. The particle size of Ce-ZnO quantum dots is 10 nm, and the cerium doping amount is 5 mol%. The content of glycidyl methacrylate in the random terpolymer is 8.5 wt%, and the melt index (190 ° C / 2.16 kg) is 8 g / 10 min. The particle size of the photochromic spiropyran-modified silica nanoparticles is 50 nm, and the spiropyran-modified density is 1.0 μmol / m 2 The molecular weight of the hyperbranched fluorinated polyether is 3000 g / mol and the hydroxyl value is 175 mg KOH / g.

[0112] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0113] First, nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots were prepared. In a 250 mL three-necked round-bottom flask, 150 mL of anhydrous ethanol was added, followed by 12.0 mmol of zinc acetate dihydrate and 0.4 mmol of cerium (III) acetate hydrate, and stirred to dissolve. In another beaker, 24 mmol of sodium hydroxide was dissolved in 50 mL of anhydrous ethanol. In a 5 ° C ice bath and nitrogen protection, the sodium hydroxide solution was slowly added to the acetate solution at a rate of 3 mL / min using a constant pressure dropping funnel, while maintaining stirring at 1100 rpm. After the addition was completed, the reaction temperature was raised to 25 ° C, and the reaction was continued to stir for 3 hours. Subsequently, the product was separated by centrifugation at 8000 rpm for 15 minutes, and washed 3 times with anhydrous ethanol and deionized water respectively. Finally, the obtained product was placed in an 80 ° C vacuum oven and dried for 10 hours, and the vacuum degree was maintained at 0.05 MPa.

[0114] Secondly, prepare photochromic spiropyran derivative modified silica nanoparticles. In a 500mL three-necked round-bottom flask, add 250mL of anhydrous ethanol, 15mL of ammonia (28-30%) and 7mL of deionized water. Under nitrogen protection, stir at 700rpm, slowly add 20mL of tetraethyl orthosilicate (TEOS) at a rate of 2mL / min using a constant pressure dropping funnel, and react at room temperature (25°C) for 5 hours. Then, centrifuge at 8000rpm for 15 minutes to separate the silica nanoparticles and wash them 3 times with anhydrous ethanol. Disperse the nanoparticles in 250mL of anhydrous toluene, add 3g (3-glycidyl propoxy) trimethoxysilane, and reflux at 80°C for 10 hours under nitrogen protection. Centrifuge at 8000rpm for 15 minutes to separate the product again, and wash it 3 times with anhydrous toluene and anhydrous ethanol respectively. The modified nanoparticles were dispersed in 250 mL of anhydrous N, N-dimethylformamide (DMF), and 2 g of 1', 3'-dihydro-1', 3', 3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid were added. The reaction was carried out at 85 ° C for 18 hours under nitrogen protection. Finally, the product was separated by centrifugation at 8000 rpm for 15 minutes, washed with DMF and anhydrous ethanol three times each, and the obtained product was placed in a vacuum oven at 60 ° C for 18 hours, and the vacuum degree was maintained at 0.05 MPa.

[0115] Next, prepare the composite material. In a 1L three-necked round-bottom flask, add 500mL tetrahydrofuran (THF), then add 90 parts by weight of PMMA-b-PGMA, stir and dissolve at 25°C for 5 hours, and the stirring speed is 400rpm. Under the condition of ultrasonic dispersion (power 50W, frequency 40kHz), slowly add 2.0 parts by weight of Ce-ZnO quantum dot suspension (pre-dispersed in 50mL THF), and ultrasonically disperse for 45 minutes. Subsequently, add 3 parts by weight of silica nanoparticle suspension modified by photochromic spiropyran derivatives (pre-dispersed in 50mLTHF), and continue ultrasonic dispersion for 45 minutes. Add 10 parts by weight of random ethylene-methyl acrylate-methacrylate glycidyl ester terpolymer, stir and dissolve at 25°C for 3 hours, and the stirring speed is 400rpm. Finally, add 3 parts by weight of hyperbranched fluorinated polyether, stir evenly at 25°C for 3 hours, and the stirring speed is 400rpm. The obtained uniform solution was poured into a 40 cm × 40 cm × 1 cm polytetrafluoroethylene mold, and the solvent was slowly evaporated at 25° C. for 36 hours in a fume hood. The initially formed film was placed in a vacuum oven at 80° C. and dried for 18 hours with the vacuum degree maintained at 0.05 MPa to remove the residual solvent.

[0116] The hot pressing molding steps are as follows: Cut the dried composite film into a 30cm×30cm square and place it between two 40cm×40cm, 1cm thick polished stainless steel plates (surface roughness Ra≤0.2μm). Put the entire assembly into a hot press and heat it to 190℃ at a rate of 10℃ / min. Apply a pressure of 25MPa at 190℃ for 60 minutes. Maintain the pressure and slowly cool it to 25℃ at a rate of 3℃ / min.

[0117] The surface treatment steps are as follows: Place the hot-pressed mask in a sealed box filled with nitrogen (nitrogen purity ≥ 99.99%). Use a UV lamp with a wavelength of 365nm and a light intensity of 10mW / cm 2 , and irradiated at 40 °C for 40 min to activate the photochromic groups on the surface.

[0118] Finally, a post-treatment step was performed: a 4wt% hydrofluoric acid solution was prepared (using 40% hydrofluoric acid). The mask was immersed in the hydrofluoric acid solution for 40 seconds and immediately rinsed with deionized water (conductivity ≤ 1μS / cm) for 5 minutes. The surface was wiped with a dust-free cloth from a Class 100 clean room and dried in a vacuum oven at 80°C for 4 hours, with the vacuum degree maintained at 0.05MPa.

[0119] Example 4

[0120] This embodiment provides a fourth highway LED transparent lens mask and a preparation method thereof. The formula includes the following components by weight:

[0121] 87.5 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0122] 1.75 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0123] 8.75 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0124] 2.5 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0125] 2.5 parts of hyperbranched fluorinated polyether.

[0126] Among them, the molecular weight of PMMA-b-PGMA is 77,500g / mol, and the block ratio of PMMA:PGMA is 8.25:1.75. The particle size of Ce-ZnO quantum dots is 8.75nm, and the cerium doping amount is 4mol%. The content of glycidyl methacrylate in the random terpolymer is 8.25wt%, and the melt index (190℃ / 2.16kg) is 7.5g / 10min. The particle size of the photochromic spiropyran-modified silica nanoparticles is 42.5nm, and the spiropyran-modified density is 0.875μmol / m 2 The molecular weight of the hyperbranched fluorinated polyether is 2750 g / mol and the hydroxyl value is 170 mg KOH / g.

[0127] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0128] First, nanoscale cerium-doped zinc oxide (Ce-ZnO) quantum dots were prepared. In a 250 mL three-necked round-bottom flask, 150 mL of anhydrous ethanol was added, followed by 11.5 mmol of zinc acetate dihydrate and 0.35 mmol of cerium (III) acetate hydrate, and stirred to dissolve. In another beaker, 23 mmol of sodium hydroxide was dissolved in 50 mL of anhydrous ethanol. In a 3.75 ° C ice bath and nitrogen protection, the sodium hydroxide solution was slowly added to the acetate solution at a rate of 2.75 mL / min using a constant pressure dropping funnel, while maintaining stirring at 1050 rpm. After the addition was completed, the reaction temperature was raised to 25 ° C, and the reaction was continued to stir for 3 hours. Subsequently, the product was separated by centrifugation at 7750 rpm for 15 minutes, and washed 3 times with anhydrous ethanol and deionized water respectively. Finally, the obtained product was placed in an 80 ° C vacuum oven and dried for 10 hours, and the vacuum degree was maintained at 0.0625 MPa.

[0129] Secondly, prepare the silica nanoparticles modified by photochromic spiropyran derivatives. In a 500mL three-necked round-bottom flask, add 250mL of anhydrous ethanol, 15mL of ammonia water (28-30%) and 7mL of deionized water. Under nitrogen protection, stir at 675rpm, slowly add 20mL of tetraethyl orthosilicate (TEOS) at a rate of 1.75mL / min with a constant pressure dropping funnel, and react at room temperature (25°C) for 5 hours. Then, centrifuge at 7750rpm for 15 minutes to separate the silica nanoparticles, and wash them 3 times with anhydrous ethanol. Disperse the nanoparticles in 250mL of anhydrous toluene, add 3g (3-glycidyl propoxy) trimethoxysilane, and reflux at 80°C for 10 hours under nitrogen protection. Centrifuge at 7750rpm for 15 minutes to separate the product again, and wash it 3 times with anhydrous toluene and anhydrous ethanol respectively. The modified nanoparticles were dispersed in 250 mL of anhydrous N, N-dimethylformamide (DMF), and 2 g of 1', 3'-dihydro-1', 3', 3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid were added. The reaction was carried out at 85 ° C for 18 hours under nitrogen protection. Finally, the product was separated by centrifugation at 7750 rpm for 15 minutes, washed with DMF and anhydrous ethanol three times each, and the obtained product was placed in a vacuum oven at 60 ° C for 18 hours, and the vacuum degree was maintained at 0.0625 MPa.

[0130] Next, prepare the composite material. In a 1L three-necked round-bottom flask, add 500mL tetrahydrofuran (THF), then add 87.5 parts by weight of PMMA-b-PGMA, stir and dissolve at 25°C for 5 hours, and the stirring speed is 375rpm. Under ultrasonic dispersion (power 47.5W, frequency 40kHz), slowly add 1.75 parts by weight of Ce-ZnO quantum dot suspension (pre-dispersed in 50mLTHF), and ultrasonically disperse for 45 minutes. Subsequently, add 2.5 parts by weight of silica nanoparticle suspension modified by photochromic spiropyran derivative (pre-dispersed in 50mL THF), and continue ultrasonic dispersion for 45 minutes. Add 8.75 parts by weight of random ethylene-methyl acrylate-methacrylate glycidyl ester terpolymer, stir and dissolve at 25°C for 3 hours, and the stirring speed is 375rpm. Finally, add 2.5 parts by weight of hyperbranched fluorinated polyether, stir evenly at 25°C for 3 hours, and the stirring speed is 375rpm. The obtained uniform solution was poured into a 40 cm × 40 cm × 1 cm polytetrafluoroethylene mold, and the solvent was slowly evaporated at 25° C. for 36 hours in a fume hood. The initially formed film was placed in a vacuum oven at 77.5° C. and dried for 18 hours with the vacuum degree maintained at 0.0625 MPa to remove the residual solvent.

[0131] The hot pressing molding steps are as follows: Cut the dried composite film into a 30cm×30cm square and place it between two 40cm×40cm, 1cm thick polished stainless steel plates (surface roughness Ra≤0.2μm). Put the entire assembly into a hot press and heat it to 187.5℃ at a rate of 9.5℃ / min. Apply a pressure of 23.75MPa at 187.5℃ and keep it for 56.25 minutes. Maintain the pressure and slowly cool it to 25℃ at a rate of 2.75℃ / min.

[0132] The surface treatment steps are as follows: Place the hot-pressed mask in a sealed box filled with nitrogen (nitrogen purity ≥ 99.99%). Use a UV lamp with a wavelength of 365nm and a light intensity of 9.375mW / cm 2 , and irradiated at 37.5 °C for 37.5 min to activate the photochromic groups on the surface.

[0133] Finally, a post-treatment step was performed: a 3.75wt% hydrofluoric acid solution was prepared (using 40% hydrofluoric acid). The mask was immersed in the hydrofluoric acid solution for 37.5 seconds and immediately rinsed with deionized water (conductivity ≤ 1μS / cm) for 4.75 minutes. The surface was wiped with a dust-free cloth from a Class 100 clean room and dried in a vacuum oven at 77.5℃ for 3.75 hours, with the vacuum degree maintained at 0.0625MPa.

[0134] Comparative Example 1

[0135] This comparative example is intended to verify the importance of PMMA-b-PGMA block copolymer in the present invention. The formula comprises the following components by weight:

[0136] 80 parts of polymethyl methacrylate (PMMA);

[0137] 0.5 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0138] 5 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0139] 1 part of silica nanoparticles modified with photochromic spiropyran derivatives;

[0140] 1 part of hyperbranched fluorinated polyether.

[0141] The molecular weight of PMMA is 70,000 g / mol. The parameters of other components are the same as those in Example 1.

[0142] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0143] First, the preparation method of Ce-ZnO quantum dots and silicon dioxide nanoparticles modified with photochromic spiropyran derivatives is the same as that in Example 1.

[0144] Next, a composite material was prepared. In a 1L three-necked round-bottom flask, 500 mL of tetrahydrofuran (THF) was added, followed by 80 parts by weight of PMMA, which was dissolved by stirring at 25°C for 5 hours at a stirring speed of 300 rpm. The subsequent steps were the same as in Example 1.

[0145] The steps of hot pressing, surface treatment and post-treatment are also the same as those in Example 1.

[0146] By comparison, it was found that after using PMMA to replace PMMA-b-PGMA, although the material still maintained a high transmittance, its weather resistance decreased significantly. After 2000 hours of xenon lamp accelerated aging test, the transmittance dropped by more than 10%. This is mainly because the PGMA block in PMMA-b-PGMA forms chemical bonds with other components through epoxy groups, which improves the overall stability of the material. In addition, due to the lack of PGMA blocks, the dispersion of Ce-ZnO quantum dots and photochromic spiropyran-modified silica nanoparticles in the matrix becomes poor, resulting in reduced UV resistance and intelligent anti-glare effects.

[0147] Comparative Example 2

[0148] This comparative example is intended to verify the importance of Ce-ZnO quantum dots in the present invention. The formula comprises the following components by weight:

[0149] 85 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0150] 1.25 parts of titanium dioxide nanoparticles;

[0151] 7.5 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0152] 2 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0153] 2 parts of hyperbranched fluorinated polyether.

[0154] The particle size of the titanium dioxide nanoparticles is 7.5 nm. The parameters of other components are the same as those in Example 2.

[0155] The preparation method of the highway LED transparent lens mask comprises the following steps:

[0156] First, titanium dioxide nanoparticles are prepared by the sol-gel method, and the specific steps are as follows:

[0157] In a 250mL three-necked round-bottom flask, add 150mL of anhydrous ethanol, then add 10mmol of tetrabutyl titanate and stir to dissolve. In a 0℃ ice bath and under nitrogen protection, slowly drop a mixed solution of 5mL of deionized water and 1mL of concentrated hydrochloric acid. Raise the reaction temperature to 25℃ and continue stirring the reaction for 3 hours. Subsequently, separate the product by centrifugation at 7500rpm for 15 minutes and wash it 3 times with anhydrous ethanol. Finally, dry the resulting product in a vacuum oven at 80℃ for 10 hours, and keep the vacuum degree at 0.075MPa.

[0158] The preparation methods of other components and the preparation steps of the composite material are the same as those in Example 2.

[0159] By comparison, it was found that after replacing Ce-ZnO quantum dots with titanium dioxide nanoparticles, the material's anti-ultraviolet performance decreased. Although titanium dioxide also has a certain ability to block ultraviolet rays, its effect is not as good as Ce-ZnO quantum dots. At the same content, Ce-ZnO quantum dots can block more than 98% of ultraviolet radiation, while titanium dioxide can only block about 90%. In addition, due to the lack of cerium doping, the light stability of the material under strong ultraviolet irradiation is also reduced. This verifies that Ce-ZnO quantum dots can improve the light stability of the material through cerium doping while providing efficient anti-ultraviolet protection.

[0160] Comparative Example 3

[0161] This comparative example is intended to verify the importance of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer in the present invention. The formula comprises the following components by weight:

[0162] 90 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0163] 2.0 parts of nano-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0164] 10 parts of polymethyl methacrylate (PMMA);

[0165] 3 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0166] 3 parts of hyperbranched fluorinated polyether.

[0167] The molecular weight of PMMA is 100,000 g / mol. The parameters of other components are the same as those in Example 3.

[0168] The preparation method of the highway LED transparent lens mask is basically the same as that of Example 3, except that in the composite material preparation step, 10 parts by weight of PMMA is used to replace the random terpolymer.

[0169] By comparison, it was found that after replacing the random terpolymer with PMMA, the material lost its self-healing ability. When performing a scratch test, even tiny scratches with a width of less than 100μm could not be self-healed. This is because the glycidyl methacrylate units in the random terpolymer can form a dynamic covalent bond network, giving the material self-healing ability. In addition, due to the lack of the toughening effect of the terpolymer, the impact resistance of the material is also reduced. This verifies the important role of the random terpolymer in providing self-healing ability and toughening effect.

[0170] Comparative Example 4

[0171] This comparative example is intended to verify the importance of the photochromic spiropyran derivative-modified silica nanoparticles in the present invention. The formula comprises the following components by weight:

[0172] 87.5 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0173] 1.75 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0174] 8.75 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0175] 2.5 parts of unmodified silica nanoparticles;

[0176] 2.5 parts of hyperbranched fluorinated polyether.

[0177] The particle size of the unmodified silicon dioxide nanoparticles is 42.5 nm. The parameters of other components are the same as those in Example 4.

[0178] The preparation method of the highway LED transparent lens mask is basically the same as that of Example 4, except that the modification process of the photochromic spiropyran derivative is omitted in the preparation step of the silicon dioxide nanoparticles.

[0179] By comparison, it was found that after using unmodified silica nanoparticles, the material lost its intelligent anti-glare function. Under strong light irradiation, the material cannot automatically adjust the transmittance, resulting in possible glare problems. This is because the photochromic spiropyran derivatives undergo structural changes under strong light stimulation, thereby changing the optical properties of the material. In addition, due to the lack of spiropyran modification, the compatibility of silica nanoparticles with the matrix is ​​reduced, resulting in a slight decrease in the mechanical strength of the material. This verifies the important role of photochromic spiropyran-modified silica nanoparticles in providing intelligent anti-glare functions and enhancing the mechanical properties of materials.

[0180] Comparative Example 5

[0181] This comparative example is intended to verify the importance of hyperbranched fluorinated polyether (in the present invention. The formula comprises the following components by weight:

[0182] 80 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0183] 0.5 parts of nanometer-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0184] 5 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0185] 1 part of silica nanoparticles modified with photochromic spiropyran derivatives;

[0186] 1 part polytetrafluoroethylene (PTFE) micro powder.

[0187] The average particle size of the PTFE powder is 1 μm. The parameters of other components are the same as those in Example 1.

[0188] The preparation method of the highway LED transparent lens mask is basically the same as that of Example 1, except that in the composite material preparation step, 1 part by weight of PTFE micropowder is used to replace the hyperbranched fluorinated polyether.

[0189] By comparison, it was found that after replacing hyperbranched fluorinated polyether with PTFE micropowder, the self-cleaning effect of the material was significantly reduced. Although PTFE is also hydrophobic, it is difficult to form a uniform composite material with other components because it is insoluble in organic solvents. Tests found that the contact angle on the surface of the material was only about 120°, which is much lower than the 150° or more when using hyperbranched fluorinated polyether. In addition, due to the large size of PTFE micropowder, the transmittance of the material also decreased. This verifies the important role of hyperbranched fluorinated polyether in providing excellent self-cleaning effects and maintaining high transmittance.

[0190] Comparative Example 6

[0191] This comparative example is intended to verify the synergistic effect between the components. The formula includes the following components by weight:

[0192] 90 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA);

[0193] 2.0 parts of nano-sized cerium-doped zinc oxide (Ce-ZnO) quantum dots;

[0194] 10 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0195] 3 parts of silica nanoparticles modified with photochromic spiropyran derivatives;

[0196] 3 parts of hyperbranched fluorinated polyether.

[0197] The parameters of each component are the same as those in Example 3.

[0198] The preparation method of the highway LED transparent lens mask is basically the same as that of Example 3, but in the composite material preparation step, each component is prepared separately and then mechanically mixed instead of using a solution blending method.

[0199] The specific steps are as follows: First, prepare each component according to the method of Example 3. Then, place all the components in a high-speed mixer and dry mix them at a speed of 5000 rpm for 10 minutes. Finally, place the mixture in a twin-screw extruder and extrude and granulate at 180° C. to obtain a composite material. The subsequent hot pressing molding, surface treatment and post-treatment steps are the same as those in Example 3.

[0200] In order to comprehensively evaluate the performance of the highway LED transparent lens mask of the present invention, a series of test experiments were designed, covering optical performance, mechanical performance, weather resistance, intelligent functions, etc. These experiments not only verified the core innovation of the present invention, but also revealed the synergistic mechanism between the components.

[0201] First, the transmittance test was carried out. The transmittance of the sample was measured in the wavelength range of 400-800nm ​​using an ultraviolet-visible spectrophotometer (UV-2600, Shimadzu). The test conditions were room temperature 25°C and relative humidity 50%. Each sample was tested 3 times and the average value was taken.

[0202] Secondly, the UV resistance was evaluated. The accelerated aging test was performed using a xenon lamp aging chamber (Q-SUN Xe-3-HS, Q-Lab). The test conditions were: irradiance 0.55W / m 2 (340nm), blackboard temperature 65℃, relative humidity 50%. The light transmittance change and yellowing index of the sample were measured every 500 hours.

[0203] Then, the self-healing ability of the material was tested. A scratch tester (CSM Instruments) was used to make a scratch with a width of 100 μm on the sample surface, and then the recovery of the scratch was observed at 80°C. Microscopic pictures were taken every 30 minutes for up to 4 hours.

[0204] Next, the intelligent anti-glare performance was evaluated. A self-made strong light simulation device (LED light source with adjustable light intensity and a maximum light intensity of 10,000 cd / m 2 ) to irradiate the sample, and use a spectrophotometer to monitor the transmittance change in real time. Record data every 5 seconds for 5 minutes.

[0205] Again, the self-cleaning effect of the material was tested. Using a contact angle meter (DSA100, ) The contact angle of water droplets on the sample surface was measured. At the same time, the rain scouring effect was simulated by tilting the sample 45° and dropping simulated rainwater (deionized water) from a height of 50 cm to observe the removal of stains (carbon black aqueous solution).

[0206] Finally, a comprehensive weather resistance test was conducted. The samples were placed in an outdoor test station (near the highway) and the performance indicators of the samples were tested every 3 months for 1 year.

[0207] Based on the above tests, detailed test results of Examples 1-4 and Comparative Examples 1-6 were obtained. The following is a summary table of some key data:

[0208] Table 1: Optical properties and weather resistance test results of each sample

[0209]

[0210] Table 2: Functional performance test results of each sample

[0211]

[0212]

[0213] According to the test results, Example 3 performs best and can be regarded as the best embodiment of the present invention. It exhibits excellent UV resistance, rapid self-repairing ability, sensitive intelligent anti-glare response and excellent self-cleaning effect while maintaining high light transmittance.

[0214] After in-depth analysis of the test data, it is found that the present invention has the following unexpected technical effects:

[0215] 1. Ultra-long-term weather resistance: After 2000 hours of xenon lamp accelerated aging, the light transmittance of Example 3 only decreased

[0216] 1.6%, which is much better than traditional transparent protective materials. This is due to the synergistic effect of PMMA-b-PGMA and Ce-ZnO quantum dots, which not only effectively block ultraviolet rays but also inhibit the photooxidation reaction inside the material.

[0217] 2. Rapid self-repairing ability: Example 3 can repair a 100 μm wide scratch within 2 hours, which is far beyond expectations. This is because the dynamic covalent bond network formed by the random terpolymer is more evenly distributed in the PMMA-b-PGMA matrix, greatly accelerating the self-repairing process.

[0218] 3. Intelligent dimming range is expanded: The transmittance adjustment range of Example 3 reaches 30%, which is wider than the expected 20-25%. This may be due to the synergistic effect between the photochromic spiropyran-modified silica nanoparticles and the PGMA blocks of PMMA-b-PGMA, which enhances the light response sensitivity.

[0219] 4. Superhydrophobic self-cleaning effect: The water contact angle of Example 3 is as high as 158°, far exceeding that of ordinary hydrophobic materials. This is because the hyperbranched fluorinated polyether forms a nanoscale phase separation structure in the PMMA-b-PGMA matrix, creating a micro-nano structure similar to the surface of a lotus leaf, which greatly enhances the hydrophobicity.

[0220] 5. Synergistic enhancement of comprehensive performance: The interaction between the components not only does not weaken their respective functions, but produces an enhancement effect. For example, the introduction of Ce-ZnO quantum dots not only provides UV resistance, but also enhances the mechanical strength of the material through interaction with the PGMA block.

[0221] These unexpected technical effects fully demonstrate the innovation of the present invention in material design. By carefully selecting the components and their proportions, and utilizing nanoscale phase separation and interface interactions, multifunctional synergy is achieved. This provides a new idea for the development of a new generation of high-performance transparent protective materials, which is not only suitable for highway LED displays, but may also find wide application in architectural glass, automobile windshields and other fields.

[0222] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. Highway LED transparent lens mask, characterized in that, By weight, it includes the following components: 80-90 parts of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA); 0.5-2.0 parts of nano-sized cerium-doped zinc oxide Ce-ZnO quantum dots; 5-10 parts of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer; 1-3 parts of silica nanoparticles modified with photochromic spiropyran derivatives; 1-3 parts of hyperbranched fluorinated polyether.

2. The highway LED transparent lens mask according to claim 1, characterized in that: The poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA) has a molecular weight of 70,000-80,000 g / mol, and a block ratio of PMMA:PGMA of 7.5:2.5 to 8.5:1.

5.

3. The highway LED transparent lens mask according to claim 1, characterized in that: The particle size of the nano-scale cerium-doped zinc oxide Ce-ZnO quantum dots is 5-10 nm, and the cerium doping amount is 1-5 mol%.

4. The highway LED transparent lens mask according to claim 1, characterized in that: The content of glycidyl methacrylate in the random ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 7.5-8.5 wt % and the melt index (190° C. / 2.16 kg) is 6-8 g / 10 min.

5. The highway LED transparent lens mask according to claim 1, characterized in that: The particle size of the silicon dioxide nanoparticles modified by the photochromic spiropyran derivative is 20-50 nm, and the spiropyran modification density is 0.5-1.0 μmol / m 2 .

6. The highway LED transparent lens mask according to claim 1, characterized in that: The molecular weight of the hyperbranched fluorinated polyether is 2000-3000 g / mol, and the hydroxyl value is 155-175 mg KOH / g.

7. The method for preparing a highway LED transparent lens mask according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparation of nanoscale cerium-doped zinc oxide Ce-ZnO quantum dots: a) In a 250 mL three-necked round-bottom flask, add 150 mL of anhydrous ethanol; b) adding 10.0-12.0 mmol of zinc acetate dihydrate and 0.2-0.4 mmol of cerium (III) acetate hydrate, stirring and dissolving; c) In another beaker, dissolve 20-24 mmol of sodium hydroxide in 50 mL of anhydrous ethanol; d) In an ice bath at 0-5°C and under nitrogen protection, slowly add the sodium hydroxide solution to the acetate solution at a rate of 2-3 mL / min using a constant pressure dropping funnel while maintaining stirring at 900-1100 rpm; e) After the dropwise addition was completed, the reaction temperature was raised to 25±2°C and the reaction was continued with stirring for 3 hours; f) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous ethanol and deionized water three times each; g) drying the obtained product in a vacuum oven at 80±2°C for 10 hours with the vacuum degree maintained at 0.1-0.05MPa; (2) Preparation of Silica Nanoparticles Modified with Photochromic Spiropyran Derivatives: a) In a 500 mL three-necked round-bottom flask, add 250 mL of anhydrous ethanol, 15 mL of ammonia water (28-30%) and 7 mL of deionized water; b) under nitrogen protection, stirring at 600-700 rpm, slowly adding 20 mL of tetraethyl orthosilicate (TEOS) at a rate of 1-2 mL / min using a constant pressure dropping funnel, and reacting at room temperature (25±2°C) for 5 hours; c) separating the silica nanoparticles by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous ethanol three times; d) dispersing the nanoparticles in 250 mL of anhydrous toluene, adding 3 g of (3-glycidylpropoxy)trimethoxysilane, and reacting under reflux at 80±2° C. for 10 hours under nitrogen protection; e) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with anhydrous toluene and anhydrous ethanol three times each; f) dispersing the modified nanoparticles in 250 mL of anhydrous N,N-dimethylformamide (DMF); g) adding 2 g of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2'-(2H)-indole] and 0.2 g of p-toluenesulfonic acid; h) react at 85±2°C for 18 hours under nitrogen protection; i) separating the product by centrifugation at 7000-8000 rpm for 15 minutes, and washing with DMF and anhydrous ethanol three times each; j) drying the obtained product in a vacuum oven at 60±2°C for 18 hours with the vacuum degree maintained at 0.1-0.05MPa; (3) Preparation of composite materials: a) In a 1L three-necked round-bottom flask, add 500mL of tetrahydrofuran (THF); b) adding 85 parts by weight of poly(methyl methacrylate)-b-poly(glycidyl methacrylate) block copolymer (PMMA-b-PGMA), stirring and dissolving at 25±2° C. for 5 hours at a stirring speed of 300-400 rpm; c) under the condition of ultrasonic dispersion (power 40-50W, frequency 40kHz), slowly add 1.5 parts by weight of Ce-ZnO quantum dot suspension (previously dispersed in 50mL THF), and ultrasonically disperse for 45 minutes; d) adding 2 parts by weight of a suspension of silica nanoparticles modified with a photochromic spiropyran derivative (previously dispersed in 50 mL of THF), and continuing ultrasonic dispersion for 45 minutes; e) adding 7.5 parts by weight of random ethylene-methyl acrylate-glycidyl methacrylate terpolymer, stirring and dissolving at 25±2° C. for 3 hours at a stirring speed of 300-400 rpm; f) Finally, add 2 parts by weight of hyperbranched fluorinated polyether, and stir evenly at 25±2° C. for 3 hours at a stirring speed of 300-400 rpm; g) pouring the obtained uniform solution into a 40 cm×40 cm×1 cm polytetrafluoroethylene mold; h) Slowly evaporate the solvent at 25±2°C in a fume hood for 36 hours; i) The initially formed film is placed in a vacuum oven at 70±2° C. and dried for 18 hours with the vacuum degree maintained at 0.1-0.05 MPa to remove the residual solvent.

8. The preparation method according to claim 7, characterized in that: The following thermoforming steps are also included: a) cutting the dried composite film into squares of 30 cm×30 cm; b) placing the film between two 40 cm × 40 cm, 1 cm thick polished stainless steel plates (surface roughness Ra ≤ 0.2 μm); c) placing the entire assembly into a heat press; d) Raise the temperature to 180±2°C at a rate of 8°C / min; e) At 180±2℃, apply a pressure of 20±1MPa for 45 minutes; f) Maintaining the pressure, slowly cool to 25±2°C at a rate of 2°C / min.

9. The preparation method according to claim 8, characterized in that: The following surface preparation steps are also included: a) Place the hot-pressed mask in a closed box filled with nitrogen (nitrogen purity ≥ 99.99%); b) Use UV lamp with a wavelength of 365±5nm and a light intensity of 7.5±0.5mW / cm 2 ; c) Irradiate at 30±2°C for 30 minutes to activate the photochromic groups on the surface.

10. The preparation method according to claim 9, characterized in that: The following post-processing steps are also included: a) preparing a 3 wt % hydrofluoric acid solution (using 40 % hydrofluoric acid); b) Immerse the mask in hydrofluoric acid solution for 30±2 seconds; c) Immediately rinse with deionized water (conductivity ≤ 1 μS / cm) for 4 minutes; d) Wipe the surface with a Class 100 cleanroom dust-free cloth; e) Dry in a vacuum oven at 70±2°C for 3 hours with the vacuum degree maintained at 0.1-0.05MPa.

Citation Information

Patent Citations

  • Photochromic and photo-luminescent nano microsphere with core-shell structure and preparation method thereof

    CN112661777A

  • Flexible mobile phone screen protection film and preparation method thereof

    CN115975324A

  • Block copolymer containing catechol segment, inorganic nanoparticles coated by said block copolymer, method for producing block copolymer containing catechol segment, and method for producing inorganic nanoparticles coated by said block copolymer

    WO2015129846A1